An investigation on the fusibility characteristics of low-rank coals and biomass mixtures. (15th October 2015) - Li, Fenghai; Xu, Meiling; Wang, Tao; Fang, Yitian; Ma, Mingjie
Highlights: Three coals were used to change ash fusion temperature (AFT) of cornstalk (CS). The CS AFT increase is not the same with the addition of different coals. AFT variations depend on the evolutions of minerals in the coal and CS at high temperature. Mullite formation in mixed ashes results in fluctuation of the AFT. Abstract: The fusion characteristics of three low-rank coals and cornstalk (CS) mixtures were investigated by ash fusion temperature (AFT) analysis, X-ray fluorescence spectrometry, scanning electron microscopy, and X-ray diffractometry. The increasing trend of CS ash fusion temperature (AFT) is not the same with the additions of different coals at the same mass ratio, due to the difference of the ash content and component of coal samples. Variations in AFTs depended on the mineral composition, which derived from mineral interaction. As the coal mass ratio increased at high temperature, Ca 2+ replaced K + in semi-molten alumino-silicate in CS ashes and led to formation of higher-melting-point anorthite, which also increased the AFT of the ash mixture. The AFT fluctuation of CS/Husheng lignite (HS) mixture during addition of HS resulted from formation of higher-MP mullite.